ANALISIS KAPABILITAS APIP DENGAN PERSPEKTIF INTERNAL AUDIT CAPABILITY MODEL (IA-CM) (Studi Kasus pada Inspektorat Kabupaten Banyumas) - Firmansyah *; Atiek Sri Purwati; Uswahtun Hasanah (Jurusan Akuntansi Fakultas Ekonomi dan Bisnis, Universitas Jenderal Soedirman, 2022)
This research is a qualitative case study. The research objective was to determine the level of capability, factors inhibiting performance capabilities, and strategies for improving the capability of APIP in Inspectorate of Banyumas. The population in this study are all structural officers, functional official auditors in Inspectorate Banyumas and also involve speakers from BPKP. The data used are primary data obtained from interviews, questionnaires, and documents as well as secondary data is a report and publication of the BPKP and Inspectorate of Banyumas. The results showed that the IA-CM capabilities of Inspectorate of Banyumas is at level 1 (initial) of 5 existing level, which means that the Inspectorate has not guaranteed its business processes in accordance with the rules and have not been able to detect the occurrence of corruption yet. The achievement of these levels is not in accordance with the National Medium Term Development Plan Year 2014-2019 that the target of APIP capability must already be at level 3 (integrated) in addition to be able to guarantee its business process and detect corruption, APIP also able to assess efficiency, effectiveness, and economy of an activity and is able to provide consulting on corporate governance, risk management and internal control. The implications of the above conclusion that in order to improve their capabilities, Inspectorate of Banyumas should make improvements that include fourteen key process areas (KPA) which is required to achieve the level 3. However, earlier must meet the requirements to achieve level 2 (infrastructure) in advance. Efforts to do are to make the proposed offering performance benefits, in coordination with the Regent and the Regional Employment Board in terms of hiring Inspectorate, planning education and training for auditors, to make way for the auditor to be a member AAIPI, guidelines on the preparation of PKPT based management priorities, budgeted work plan at 1 percent of the expenditure budget, and prepare SOPs related to the preparation of the Internal audit Charter and procedures for requesting audit data needs.